2023
DOI: 10.1111/cobi.14083
|View full text |Cite
|
Sign up to set email alerts
|

Review of hyperdispersal in wildlife translocations

Abstract: Species translocation is a common tool to reverse biodiversity loss, but it has a high failure rate. One factor that contributes to failure is postrelease hyperdispersal, which we define as the long‐distance movement of individuals resulting in their failure to contribute to population establishment. We reviewed reported incidences of hyperdispersal and compared rates of hyperdispersal among taxa, population demographics, release cohorts, and success of mitigation techniques. Of 151 conservation translocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…For populations that have been translocated into new areas, natal dispersal may be particularly risky. Subadults moving into unoccupied habitat will not benefit from conspecific cues alerting them to suitable habitat and thus may disperse into unknown habitat and outside of areas under intensive management (Bilby & Moseby, 2023; Stamps & Swaisgood, 2007). Disturbances from habitat fragmentation, physical barriers, and increased mortality during dispersal are likely to lead to reduced gene flow and inbreeding within a population (Banks et al., 2005; Frankham et al., 2014; Levy et al., 2013) which may also affect the long term sustainability of reintroduced populations.…”
Section: Introductionmentioning
confidence: 99%
“…For populations that have been translocated into new areas, natal dispersal may be particularly risky. Subadults moving into unoccupied habitat will not benefit from conspecific cues alerting them to suitable habitat and thus may disperse into unknown habitat and outside of areas under intensive management (Bilby & Moseby, 2023; Stamps & Swaisgood, 2007). Disturbances from habitat fragmentation, physical barriers, and increased mortality during dispersal are likely to lead to reduced gene flow and inbreeding within a population (Banks et al., 2005; Frankham et al., 2014; Levy et al., 2013) which may also affect the long term sustainability of reintroduced populations.…”
Section: Introductionmentioning
confidence: 99%
“…Post-release movements can determine the survival of translocated animals by shaping how they acquire information or encounter risks. Exploratory movements are very common in many taxa (Gouar et al, 2008a;Linklater & Swaisgood 2008;Pinter-Wollman 2009;Marques et al, 2011;Nussear et al, 2012;Pille et al, 2018;Griffith et al, 2019;Bilby & Moseby 2023). However, some animals remain in the vicinity of the introduction area post-translocation (Nafus et al, 2017;Garnier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in achieving successful CI arises from an incompatible habitat at the release site compared with the habitat of origin [18,19]. A global review of CI success found that habitat-related factors were the largest drivers of initial declines for birds and other taxa released in novel habitats [2].…”
Section: Introductionmentioning
confidence: 99%